Colonial Hong Kong and modern China : interaction and reintegration - Lee, Pui-tak (Hong Kong University Press, 2005)
The evolution of Hong Kong, as a British colony and now a Special Administrative Region at China's door step, has always been inextricably intertwined with the situation in China. This relationship is examined through various perspectives in this volume.